Unraveling the regional environmental ecology dominated baijiu fermentation microbial community succession and associated unique flavor - Wu, Xiaowei; Zhao, Xiaoli; Wang, Li; Chen, Bi; Li, Fangzhou; Tang, Zhi; Wu, Fengchang (Frontiers in Microbiology, 2024)
Chinese baijiu as one of the famous distilled liquor in which fermented in open environments, with various microorganisms (i.e., bacteria, fungi, and yeast) involved in their brewing process, and created corresponding unique flavor. However, the sources of environmentally enriched microbial communities associated with liquor fermentation are still being characterized yet. Given the dependence of microbial growth and reproduction on environmental ecology, it is important to understand the correlation between baijiu fermentation microbial community and surrounding environmental ecology (i.e., temperature, humidity, wind, and precipitation). This study systematically overviewed the sources of microorganisms in the Jiang-flavor-Baijiu fermentation system. The results showed that microorganisms in baijiu brewing (i.e., mold, lactic acid bacteria, and yeast) mainly originated from surrounding environmental matrices, including the air (i.e., Yeast, Streptomyces and Bacillus), soil (i.e., Xanthomonas, Methanococcus and Comamonas) and water (i.e., Flavobacterium, Acinetobacter, and Pseudomonas) via atmospheric transport, raw material transfer and surface runoff. In addition, the unique baijiu fermentation microbial community diversity depends on local geology and meteorological conditions, highlighting that the structural stability and diversity of the microorganisms in the Baijiu brewing process dominated by local environmental ecology. We also explored the regional environmental conditions on the microbial community and found that the unique Jiang-flavor-Baijiu fermentation microbial community diversity depends on local geology and meteorological conditions. The Jiang-flavor-Baijiu workshop is located in the basin of the middle- and low latitude mountainous areas, with sufficient solar irradiation and rainfall, high air humidity, and low wind speed that favor the growth and propagation of Baijiu fermentation microorganisms. Therefore, the obtained conclusions provide new insights unraveling the key factor controlling the unique flavor of Chinese Baijiu, where protecting the ecology of baijiu brewing-regions is fundamental for maintaining the long-term quality of baijiu.